1963
DOI: 10.1002/ardp.19632960207
|View full text |Cite
|
Sign up to set email alerts
|

Über Inhaltsstoffe des Rhizoms von Geranium palustre L.

Abstract: ober Inhaltsstoffe des Rhizoma vom Geranium palustre L.B en z o y 1 k e t e n -0il t h y 1 -Np h e n y 1 -0, Nace t a1 (VII) Herstellung analog V aus I (2,l g) und Anlin (1,0 g). Das Rohkristallisat (2,5 g) wird auf dem Tonteller getrocknet, aus wenig Methanol rekristallisiert und mit Ather gewaschen. Hellgelbe Kristalle vom Schmp. 76,5-77,5'. Die methanolimhe Losung gibt rnit Eisen(II1)chlorid eine schwache, griinliche Fiirbung.C1,H,,NO2 (267,3) 0,5 g Oxalylketen-metal") mit der Mischung von 1 ml Dibenzylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1964
1964
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Most of them are believed to be hydrolyzable gallo-and ellagitannins (Blinova, 1954). Free EA and GA have also been isolated from the plants (Gstirner and Widenmann, 1964;Panizzi et al, 2000). G. rivale and G. urbanum could be rich sources of EA and GA and this might be reflected in their activity.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are believed to be hydrolyzable gallo-and ellagitannins (Blinova, 1954). Free EA and GA have also been isolated from the plants (Gstirner and Widenmann, 1964;Panizzi et al, 2000). G. rivale and G. urbanum could be rich sources of EA and GA and this might be reflected in their activity.…”
Section: Introductionmentioning
confidence: 99%
“…Only several studies have reported the isolation of chemical constituents of G. urbanum. To date, 16 flavonoids have been isolated from this plant [15][16][17][18], 21 ellagitannins [15][16][17][18][19], 15 phenylpropanoids [15-18, 20, 21] and 2 triterpenoids [18]. According to the literature data, the beneficial effects on the gastrointestinal tract are due to the high content of gallic and ellagic acids, while gemin A has a styptic effect [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that (+)-eatechin and (--)-epicatechin have been isolated from the roots of meadow geranium (Geranium pratense) and (+)-eatechin, (--)-epicatechin, and(±)-gallocatechin from the roots of Geranium palustre [3].…”
mentioning
confidence: 99%